Legal and Administrative Strategies for Addressing Military Administrative Offences within the Personnel of the State Border Guard Service of Ukraine - Kushnir, Yaroslav (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
This study examines the role of the State Border Guard Service of Ukraine in preventing administrative military violations during the ongoing state of martial law. The research emphasizes the growing importance of optimizing the efficiency and functionality of border control agencies amid heightened security challenges. Using a qualitative research method with a juridical-normative and comparative approach, the study explores legal frameworks, institutional practices, and foreign experiences to identify best practices for Ukraine. Using a literature review, legal documents, government decrees, and international conventions on border protection are systematically reviewed to determine the legal basis and administrative procedures governing preventive measures. Meanwhile, the comparative qualitative analysis involves examining case studies from other countries that have implemented effective systems for preventing administrative offenses in border services. In addition, qualitative interviews with border officials, legal experts, and defense policymakers were conducted to gain practical insights into the challenges faced in enforcing administrative discipline under martial law. The findings reveal that while Ukraine has a solid legal foundation for border protection, gaps remain in coordination, documentation, and personnel training. Drawing on both domestic and international perspectives, the study identifies adaptable mechanisms to enhance the efficiency of combating administrative and military offenses. Ultimately, this research offers policy recommendations to improve preventive measures, strengthen legal accountability, and ensure that Ukraine’s border security system remains resilient, transparent, and compliant with international norms during periods of military emergency.